If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 7y + -3y = 42 Combine like terms: 7y + -3y = 4y 4y = 42 Solving 4y = 42 Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Divide each side by '4'. y = 10.5 Simplifying y = 10.5
| 6=-5w+3(w-4) | | 12+20=-13 | | 6x+16+2x+48=180 | | -19=-4+9(h-8) | | 6=-5w(w-4) | | 53.00-p=14.50 | | 6b^2+16b-9=0 | | 9(n+3)=6n-3 | | 3x+(4x-20)+(2x+20)=180 | | 11x+17=13x+1 | | -12x+7=-7x+18 | | 3p+3=-3 | | 6x-48=11x+97 | | 10x-29=-18x+19 | | 9m-35=2m | | 22+7c=71 | | 3(x-1)=-3x+9 | | 51-6h=-3h | | A=3.14*324 | | 4(-8-6x)=88 | | (2x+1)2=x | | 5(k-22)=56 | | 11x+17=13+1 | | m(x)=-2x-3 | | 2n-n=6-5n | | 10(x+3)-(-9x-4)=2(x-10)+3 | | 6*z+.36=24.72 | | 12k^2+31k+20=0 | | 35+8x=18x+5 | | 12+6x=3(4+2x) | | 5x+9x=232 | | -2.2+22.2=-1.7+3(8t-0.9) |